Evaluación del comportamiento en cosecha y poscosecha de dos ecotipos de chocho (Lupinus mutabilis Sweet), nativo y peruano a diferentes índices de cosecha en la provincia de Cotopaxi, periodo 2020 – 2021 - Caisaguano Ugsha, elson Ramiro (2021)
The present investigation in its field phase was carried out in the Píllaro Canton, Tungurahua Province located at an altitude of 2,750 m.a.s.l. with west longitude of 78 ° 32'22 "and with south latitude of 01 ° 11'28" where it was evaluated in harvest: percentage of plants with central inflorescence, number of lateral inflorescences, number of pods of the central axis, number of seeds, length of the central axis respectively for each ecotype. Likewise, the pod and seed color were characterized using the Munsell table of plant tissues. Likewise, the post-harvest phase was established in the laboratories of the Technical University of Cotopaxi, in the Experimental Campus of Salache, Barrio Eloy Alfaro, in the Canton of Latacunga, Province of Cotopaxi, located at an altitude of 2725 m.s.n.m. with west longitude of 78º37'14 '' and with south latitude of 00º59'57 '' in which the following indicators were evaluated consecutively such as pH, firmness, humidity, weight, ash and percentage of alkaloids of each index, taken after obtaining the treatments under study. With the objective of studying the evaluation of the behavior in harvest and postharvest of two ecotypes of (Lupinus mutabilis sweet), native and Peruvian at different harvest indices in the province of Cotopaxi, period 2020-2021. For the evaluation of the ecotypes in the field, an experimental design of complete random blocks was applied, which consists of a (DBCA) with a 2 * 5 Factorial Arrangement, with a total of 10 treatments with 3 repetitions, which is equivalent to 30 units. experimental. Each treatment corresponds to the Ecotype and chronological index of the crop.In addition, with the use of the statistical program Infostat, the analysis of the data obtained was carried out, where the best treatment was established, and it was determined that in the harvest stage, the local ecotype peruano reached the percentage of Percentage of plants with central inflorescence had an average of 29% at 113 days after sowing and in the number of lateral inflorescences it obtained an average of 10.5 in its lateral branches at 135 days, also in the length of the central axis an average of 35.6 cm in length was obtained at 169 days, also in number of pods in the central axis it obtained an average of 17.63 pods in the bush at 169 days and also with an average 4.55 number of seeds in each pod at 192 days. In the postharvest stage, the best treatment was t7 on days 1 and 4, with Peruvian Ecotype with index 4 (Cream) with the following, 2.5 GY 8/8 in pod and 2.5 GY 8/10 in seed. In the same way, obtaining that the physicochemical parameters achieve the following results; with a weight of 0.91 gr, firmness of 8.29 lb / in2 and a pH of 6.31, a humidity of 70%, an ash of 30.3% and an alkaloid of 0.55% was superior,%. These parameters are within the permissible limits stipulated by the (NTE INEN 2390, 2004) regulates that the grain of lupine debittered for human consumption must comply with the physicochemical parameters such as: humidity 72.00-75.00%, ashes 19 -25%, alkaloids 0.2- 0.7%. A cost analysis of the best treatment was also developed, where T6 has a lower production cost is green in which we have a color of 2.5 GY 5/8 in pod and in seed 2.5 GY 5/8 and lime green obtains a color of 2.5 GY 6/8 in pod and in seed 2.5 GY 6/10 harvested at 180 days, in the same way as a possible introduction in the market would be viable. In conclusion, the Peruvian Ecotype is very early in terms of its phenological development and according to the cost analysis, the best treatment is T6 with its Green harvest index of $ 39.92 and it is harvested at 180 days, in the same way a possible introduction to the market would be feasible.